A Practical Guide to the NEC3 Engineering and Construction Contract - Rowlinson, Michael (Wiley-Blackwell, 2011)
"Launched in 1991, the New Engineering Contract (NEC) has become one of the UK's leading standard forms of contract for major construction and civil engineering projects. Currently in the third edition, popularly known as NEC 3, it is a process based construction contract embodying project management best practice, and thus the basic philosophy behind the contract is different to the more adversarial principles and approach of other standard construction contracts. Written as a practical guide to the application of the procedures contained in NEC 3, this book will aid users in the transition from their use and understanding of the other standard construction contracts to the collaborative project management based approach of the ECC. Written for anyone working in the construction industry working on a project under the ECC, it will be of interest to the complete construction supply chain including employers, construction professions, contractors and sub-contractors. It will also be of interest to consultants and lawyers advising any of these parties, either in the preparation of contract documentation or the resolution of problem situations which may arise. A practical guide to the application of the procedures contained in the NEC Engineering and Construction Contracts Written specifically for people actually using and administering the NEC contracts - rather than lawyers Covers all the variations created by the Main and Secondary Options Reviews all the other contracts available within the NEC3 suite"--